Istikṣāf adawāt al-Tamāsuk al-Nahwi wa al-mu’jamī bii’tibārihā buniyah ‘ala insijam al-Nusūs liāyāti al-Tasāmuh al-Dīnī (dirōsatu tahlīli al- Khithōbi fi al-Qur’āni al-Karīmi) - Afif Kholisun Nashoih; Syamfa Agny Anggara; Moh. Ubaidillah; Muhammad Ichsan (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
The Qur'an is quite different from most general texts. Among the most prominent differences is that it is said that the Qur’an includes elements of the discourse structure that lead to the harmony and unity of the texts. Therefore, this simple article is written with the aim of describing the textual harmony of the verses of religious tolerance in the Holy Qur’an - which are spread in 7 chapters - by applying the theory of discourse analysis promoted by Halliday & Hasan. In particular, this research aims to explore cohesion tools, whether grammatical or lexical. To achieve these desired goals, the researchers used observations followed by note-taking techniques to collect data. In conducting data analysis, the "padan intralingual" method is used, which he makes use of to connect the linguistic elements. The results of the research show that the signs of cohesion in the verses of tolerance at the grammatical cohesion level are achieved by references, substitutions, ellipsis, as well as a conjunction. As for lexical cohesion, signs of cohesion are achieved through synonymy, antonymy, repetition, hyponymy, and collocation. These tools not only make the texts of the verses coherent but also make them coherent and interdependent. However, there are very few sentences that seem incoherent. In this case, it is not enough to understand the theory of coherence alone, until what is known as the "knowledge of the world" (knowledge of the world) that can be realized through theoretical or applied language sciences is required.